AI-Enhanced Business Model Canvas for Sustainable Tourism - Rosy Aprieza Puspita Zandra; Santi Widhiyanti (Journal of International Conference Proceedings, 2025)
This study extends previous research on the Plaza Bukit Surga tourism destination, which previously utilized the Business Model Canvas (BMC) and SWOT analysis to identify weaknesses in marketing and resource utilization. To enhance strategic decision-making, this study integrates Artificial Intelligence (AI) into the BMC framework, resulting in an AI-Enhanced Business Model Canvas for sustainable tourism development. Data were derived from prior research conducted between 2022 and 2024, including visitor and revenue data, combined with recent Google Maps reviews collected in 2025. The reviews were analyzed using AI to identify patterns in visitor perception. Findings reveal that 83,50% of visitors express positive sentiment highlighting natural scenery, hospitality, and affordability, while negative sentiments focus on accessibility and facility maintenance. Integrating AI-driven insights into the BMC enhances the Customer Relationship, Value Proposition, and Revenue Streams components, producing a more adaptive and data-driven business model. The study demonstrates that combining traditional qualitative approaches with AI sentiment analytics can strengthen strategic planning and support sustainable management in community-based tourism destinations.